Semiconductor productivity gains linked to multiple innovations. - Sieling, Mark Scott (Monthly Labor Review, 1988)
Major gains in productivity realized between 1972 and 1981 in the semiconductor industry were generated mainly by quick advances in product design and manufacturing techniques and processes. During the first half of the 1980s, gains in output per employee hour fell to one quarter of those made in the 1970s, due to increasing Japanese competition and slowdowns in computer manufacturing, a major market for semiconductor devices. Although semiconductor output has recovered from a 1985 downturn, long-term industry growth will depend primarily on the industry's ability to quickly make marketable products out of laboratory discoveries.